1986
DOI: 10.1111/j.1465-7287.1986.tb00843.x
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Considerations in Cable Television Franchising

Abstract: Franchising and renewing of franchises for cable television systems is an important urban policy issue. Of particular interest is whether franchise authorities ought to grant more than one franchise to provide cable service in a given area. This paper reports results of an empirical investigation into the cost structure of large, modern, urban cable systems. We find modest economies of scale in dimensions relevant to the feasibility of direct competition. The economies are not so large as to rule out the possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…2 A small number of traditional cable overbuilders have had an impact on incumbent cable operators in a limited number of local communities. However, the economics of laying cable down the same street as the incumbent cable provider to compete as an overbuilder continue to be difficult (See Noam, 1985;Owen and Greenhalgh, 1986;Johnson, 1994;Rizzuto and Wirth, 1998;Neel, 2002).…”
Section: Industry Overviewmentioning
confidence: 98%
“…2 A small number of traditional cable overbuilders have had an impact on incumbent cable operators in a limited number of local communities. However, the economics of laying cable down the same street as the incumbent cable provider to compete as an overbuilder continue to be difficult (See Noam, 1985;Owen and Greenhalgh, 1986;Johnson, 1994;Rizzuto and Wirth, 1998;Neel, 2002).…”
Section: Industry Overviewmentioning
confidence: 98%
“…They found that larger cities generally do not have lower costs, although larger audiences allow a greater number of channels so that cost per subscriber per channel is somewhat less in the larger systems. The traditional scale economies argument for natural monopoly fails to impress the authors: "prices for cable services do not in fact vary substantially with city size" (Owen and Greenhalgh 1986).6 Their study does, however, find significant density economies. A single cable firm is estimated to have 14 percent lower costs than would two overlapping firms in serving a given number of subscribers in a given area-under the assumption that dual firms serve 50 percent market shares (Owen and Greenhalgh 1986).…”
Section: Economies Of Scalementioning
confidence: 86%
“…On this important issue, Owen and Greenhalgh (1986) report statistical evidence revealing economies of density, as opposed to economies of scale. They found that larger cities generally do not have lower costs, although larger audiences allow a greater number of channels so that cost per subscriber per channel is somewhat less in the larger systems.…”
Section: Economies Of Scalementioning
confidence: 99%
“…LOGHOMES is included as an explanatory variable to account for possible economies of scale (Noam 1985;Owen and Greenhalgh 1983). LOGHOMES is predicted to have a negative effect on BPPCH and PPRICE.…”
Section: The Importance Of Internal Reputation In Cable Markets Is Nomentioning
confidence: 99%